The Foreign Currency Market Analysis: Emerging Market of Muslim Countries - Dewi Mahrani Rangkuty; Kiki Farida Ferine (Journal of Islamic Economics (JoIE), 2022)
This study aims to analyze the relationship between Exports, Inflation, Money Supply, GDP, Imports, and Per capita Income to exchange rates. Where variable monetary policy (Exchange Rate, GDP, Money Supply, Inflation, Per capita Income) and macro policy (Export and Import). Using time-series data from 2010 to 2019. The data analysis model is a Vector Autoregression method viewed and sharpened by Impulse Response Function analysis and Forecast Error Variance Decomposition. The results of the IRF analysis know that the response stability of all variables is formed in the five or medium or medium-term and long-term periods, where the response of other variables to changes in one variable shows different variations from positive to negative responses or vice versa. Some variables show a positive reaction or remain negative in short to long term. The results of the FEVD analysis show that variable exchange rates in the short and medium term are recommended by the Variable Exchange Rate itself and the Money Supply Amount. At the same time, the long term is affected by Imports. Export variables in the short term are recommended by the Exchange Rate, while the medium and long term is affected by Per capita Income. Then, import variables in the medium and long short term Imports are affected by Exports. Variable GDP in the short and medium-term is influenced by GDP itself and the exchange rate, while in the long run, it is influenced by Per capita income. Inflation in the medium and long short term is affected by imports. The money supply in the medium and long short term is affected by inflation and imports, while exports influence per capita income in the short, medium, and long time. So that can be recommended in this study is as input for the government, namely through Bank Indonesia, the Ministry of Finance, the Central Banks of the State, which is the object of research in controlling exchange rates as an effort to maintain currency market stability in emerging markets of Muslim Countries through inflation control to increase price stability that can boost economic growth.